1996
DOI: 10.1111/j.1460-9568.1996.tb01617.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D1 Receptor‐mediated Facilitation of GABAergic Neurotransmission in the Rat Strioentopeduncular Pathway and its Modulation by Adenosine A1 Receptor‐mediated Mechanisms

Abstract: By using in vivo microdialysis it was found that one of the main functions of striatal dopamine D1 receptors is to selectively facilitate GABAergic neurotransmission in the 'direct' strioentopeduncular pathway. D1 receptors localized in the entopeduncular nucleus were also found to facilitate GABA release. However, results obtained from in vivo microdialysis, in vivo electrochemistry, immunohistochemistry and confocal laser microscopy suggested that entopeduncular D1 receptors could only be activated under pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 136 publications
(74 citation statements)
references
References 40 publications
1
73
0
Order By: Relevance
“…These changes in paired-pulse ratio indicate a presynaptic locus for the A 1 receptors regulating glutamatergic synaptic transmission in the NAcc. Although A 1 receptor mRNA has been located in a minority of striatal neurons (Ferré et al, 1996), postsynaptic A 1 receptors play no obvious role in the effects of adenosine, NMDA, and dopamine described here. Thus glutamate release is likely to be inhibited presynaptically not by D 1 receptors, but by A 1 receptors, which are activated indirectly by dopamine.…”
Section: Discussionmentioning
confidence: 57%
“…These changes in paired-pulse ratio indicate a presynaptic locus for the A 1 receptors regulating glutamatergic synaptic transmission in the NAcc. Although A 1 receptor mRNA has been located in a minority of striatal neurons (Ferré et al, 1996), postsynaptic A 1 receptors play no obvious role in the effects of adenosine, NMDA, and dopamine described here. Thus glutamate release is likely to be inhibited presynaptically not by D 1 receptors, but by A 1 receptors, which are activated indirectly by dopamine.…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies showed evidence for an opposite modulatory role of adenosine in the other major striatal neuronal element, the GABAergic dynorphinergic neuron, where activation of A 1 receptors attenuates dopamine D 1 receptor-mediated release of GABA and increase in the striatal expression of the immediate-early genes NGFI-A, c-fos and jun-B (Ferré et al, 1996. Therefore, under physiological conditions of increased adenosine release, a preferential activation of GABAergic enkephalinergic vs GABAergic dynorphinergic neurons must take place.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, stimulation of A 1 receptors, but not A 2A receptors (Sebastiao and Ribeiro 1996), inhibits the release of glutamate (Fredholm 1995) and decreases the extracellular levels of dopamine (Zetterström and Fillenz 1990;Ballarin et al 1995;Okada et al 1996), acetylcholine (Bueters et al 2003), and GABA (Ferré et al 1996). Adenosine-induced reductions in these or other intercellular messenger substances could in turn affect glial KYNA synthesis by impairing the signaling of distinct astrocytic membrane receptors (Steinhäuser et al 1994;Zanassi et al 1999;Khan et al 2001;Sharma and Vijayaraghavan 2001;Zhou and Kimelberg 2001;Araque et al 2002).…”
Section: Discussionmentioning
confidence: 99%